Geo-Congress 2014 Technical Papers 2014
DOI: 10.1061/9780784413272.411
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Evaluation of Thermally Induced Strain and Corresponding Lateral End Pressures for a GRS IBS in Ohio

Abstract: Geosynthetic-Reinforced Soil (GRS) Integrated Bridge Systems (IBS) integrate conventional bridge superstructures with a GRS abutment foundation and GRS approach for a cost effective, rapid construction alternative. A 42.7 m long single span GRS IBS was constructed and instrumented to monitor the thermally induced behaviors and better understand the interaction between the superstructure and substructure within the limits of this system. Strain gages were attached to the steel girders and lateral end pressures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Researchers have conducted field monitoring to investigate the long-term performances of the GRS-IBSs under working stress conditions. Results showed that the GRS-IBSs have good service performances and significant advantages in eliminating bumps at the end of the bridge slabs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have conducted field monitoring to investigate the long-term performances of the GRS-IBSs under working stress conditions. Results showed that the GRS-IBSs have good service performances and significant advantages in eliminating bumps at the end of the bridge slabs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%